THE TRAINING PROCESS AS A CONTINUOUS METHOD OF INCREASING THE DEVELOPMENT OF ENDURANCE - Andreea ANDREI; Bianca CHERA FERRARIO (Cluj University Press, 2019)
Aim: 5-6 years of training are necessary to obtain maximum results in freestyle wrestling. In order to reach a superior level, it is essential that effort should increase progressively within the training process. Objectives: Studying evolution of strength and resistance of athletes in specific actions in freestyle wrestling, Analysing training organisation through effort methods, Studying and analysing execution techniques in sessions against the clock Methods: Dummy throws; going into the bridge position, duration. Results: The recorded results point to an ascending evolution of values, which emphasises an improvement of the overall execution technique in better endurance conditions. Conclusions: Through constant and sustained training, we have achieved good progress, which shows that efficient means and correct methods of training were employed. Furthermore, the execution technique has also improved as a result of a large number of repetitions per time unit. REZUMAT. Procesul de antrenament ca modalitate continuă de dezvoltare ascendentă a rezistenţei. Pentru obţinerea unor rezultate maxime în lupte libere sunt necesari 5-6 ani de pregătire. Pentru a atinge un nivel superior este necesar ca în cadrul procesului de antrenament creşterea efortului să se facă progresiv. Obiective: Studierea evoluției forței și a rezistenței sportivilor în acțiunile specifice din lupte libere, Analiza organizării antrenamentelor pe mijloace de efort, Studierea și analiza tehnicii de execuție în acțiuni contra-timp. Metode: Aruncări cu manechinul; Intrări în pod, durata. Rezultatele indică o evoluție ascendentă a valorilor, fapt ce evidențiază o îmbunătățire a tehnicii globale de execuție într-un regim de rezistență mai bun. Concluzii: Prin antrenament repetat și susținut am obținut o linie de progres bună, care demonstrează că s-au folosit mijloace eficiente și metode corecte de antrenament. De asemenea s-a îmbunătățit și tehnica de execuție, printr-un număr mai mare de repetări pe unitatea de timp.   Cuvinte-cheie: lupte libere, rezistență, cadeți.